Kritik Sosial dalam Cerpen “Dari Masa Ke Masa” Karya A.A. Navis: Tinjauan Sosiologi - Agust Furi Kartika Panjaitan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Literature serves as a medium for reflection and social criticism of societal realities. Based on this function, this study examines social criticism in the short story